Impact of the MSU-Sulu College of Agriculture's Patikul Extension Program on Local Students - . Sammah, Merhama M.; Marajuli, Fatima Sheirene M.; Sammah, Ronnie H.; Ahajani, Nedzfa A. (Future Science / FSH-PH Publications, 2024)
This study examined the positive impacts of the MSU-Sulu Col-lege of Agriculture's Patikul Extension Program on students from Patikul Municipality. It focused on three key areas: socio-cultural, economic, and environmental aspects. Data was collected through a structured survey, which included two sections: one for demo-graphic information and another for assessing program impacts. The responses were analyzed using weighted means, inferential statistics, and one-way ANOVA to identify significant differences across respondent profiles.Key findings revealed that most respondents were female, aged 25 or older, and first-year students. In terms of impact, the socio-cultural aspect had the highest rating (4.58,